K3 RISK ANALYSIS IN PESTICIDE USE LOCAL AND TRANSMIGRATION VEGETABLE FARMERS IN PURWODADI VILLAGE, KUALA PESISIR DISTRICT, NAGAN RAYA REGENCY - Ladani; Jun Musnadi; Firman Firdauz Saputra; Dian Fera; Rismawati (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Pesticides are chemical compounds used in controlling plant pests. The use of pesticides not in accordance with the threshold value can cause health risks for farmers. This study aims to analyze the phenomenon of pesticide use patterns, the risk of Occupational Diseases (PAK) due to pesticide exposure, and the pattern of use of Personal Protective Equipment (PPE) in local farmers and transmigration farmers in Purwodadi village. The approach used in this study is a qualitative method with a phenomology design, in-depth interview data collection techniques, participatory observation and documentation, with interview guidelines starting from the pattern of pesticide use that will explore the types of pesticides and how to use them, then explore the symptoms of diseases caused by pesticides in farmers and the use of PPE, by exploring experiences and reasons for using PPE. The results of this study indicate that local farmers are better at managing the dose and time of pesticide spraying than transmigration farmers, who often use excessive doses due to lack of knowledge. The risk of PAK in local and transmigration farmers is at risk of cardiovascular disease, COPD, cancer and dermatitis with symptoms felt by farmers, although local farmers tend to know the risks of pesticide exposure, and transmigration farmers consider only factors of work fatigue and age. The use of PPE among farmers is still low, especially among transmigration farmers due to economic factors and discomfort.